Herrevolution: Empowering Women Freelancers - Patidar, Chandra Prakash (International Journal of Computer Sciences and Engineering, 2022)
Women play a significant role in uplifting the economy of every other country in the world today. We can take the example of Japan where women used to have very little share in the economy as they were mostly housewives but slowly and Steadily they started to progress when the government increased their involvement via employment schemes. As the name suggests Herrevolution is a website meant to empower women who are freelancers Mainly housewives to sell their products and reach out to the world with their inspiring Stories. It also provides a platform for an organization that deals with a technical aspect which can benefit from the business. Web Technology which is the foundation of our project is a rapidly advancing industry where new technologies are arriving day by day like Reacts and Angular as frontend technologies which are dynamic in nature and backend technologies like Nodejs and MongoDB. This paper contains details about how our website works and various aspects related to it and what impact it will have [1].